Promote Knowledge, Develop Prototypes of Bamboo Woven Products to Enhance the Grassroots Economy Elderly Group, Chiang Klom Subdistrict Municipality, Pak Chom District, Loei Province - Adirutchotsiri, Kunkhanit (Journal of Graduate MCU KhonKaen Campus, 2025)
This academic article aims to develop the potential of knowledge transfer, local wisdom of bamboo weaving among the elderly group with occupation and income, to develop bamboo weaving prototypes among the elderly group and set guidelines. Strengthening local wisdom among the elderly by going to the Elderly Quality of Life. There have been activities to develop prototypes of 5 bamboo weaving machine products. Development and Career Promotion Center, Chiang Klom Subdistrict Municipality, with 50 elderly people participating in the project. And there is training to improve and develop the group's products by inviting product design experts to train to provide knowledge in pattern design and selection of materials suitable for product patterns. To add value to bamboo woven products, the elderly group has exchanged knowledge and implemented activities according to the group's needs and the group members want to train on how to develop products of higher quality in order to apply for community product standards in the future.